2019
DOI: 10.1021/acs.iecr.9b03965
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastrong Interaction and High Dispersibility of TS-1 on Polymer-Modified Carbon Nanotubes/Nickel Foam

Abstract: In this paper, monolithic TS-1 (a zeolitic material containing both silicon and titanium) was successfully synthesized on polymer-modified carbon nanotubes/nickel foam (PMTS-1). PMTS-1 had high surface areas and aggregated pores (confined pores formed in an aggregated structure), and TS-1 could be evenly dispersed on the surface, which could facilitate reactant transport and improve dispersibility of TS-1. TS-1 strongly interacted with the polymer-modified CNTs/NF and is highly dispersed because the PDDAmodifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…A negative interaction energy corresponds to attraction, and the lower the interaction energy, the stronger the attraction. [ 35 ] As shown in Figure 5, the E interaction of model II for plasticized PVC composite incorporated with both TiO 2 @ZnAlSn and PETMP is −68 024 kcal mol −1 , which is lower than that of model I for plasticized PVC composites incorporated with only TiO 2 @ZnAlSn (−67 266 kcal mol −1 ). Thus, it is concluded that incorporation of PETMP can strengthen the interaction between the surface of TiO 2 @ZnAlSn and the PVC‐based matrix, which is possibly due to the strong interactions between “C–Cl” groups in PVC and “–SH” groups in the healing agent.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…A negative interaction energy corresponds to attraction, and the lower the interaction energy, the stronger the attraction. [ 35 ] As shown in Figure 5, the E interaction of model II for plasticized PVC composite incorporated with both TiO 2 @ZnAlSn and PETMP is −68 024 kcal mol −1 , which is lower than that of model I for plasticized PVC composites incorporated with only TiO 2 @ZnAlSn (−67 266 kcal mol −1 ). Thus, it is concluded that incorporation of PETMP can strengthen the interaction between the surface of TiO 2 @ZnAlSn and the PVC‐based matrix, which is possibly due to the strong interactions between “C–Cl” groups in PVC and “–SH” groups in the healing agent.…”
Section: Resultsmentioning
confidence: 97%
“…Then, the layer builder was used to form a PVC‐based matrix over the surface, and its interfacial interaction with TiO 2 @ZnAlSn was analyzed. The interfacial interaction was obtained from the following equation [ 35 ] : Einteractiongoodbreak=Etotalgoodbreak−()ELDHgoodbreak+Ematrix, where E total is the surface energy of LDH with PVC‐based matrix, E LDH is the surface energy of LDH without PVC‐based matrix, and E matrix is the energy of the PVC‐based matrix without LDH surface.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, our research group has conducted in-depth research. Zhang et al used the CVD method to grow the CNT layer in situ on the surface of FN and then loaded TS-1 nanoparticles by the hydrothermal method. TS-1 nanoparticles are highly dispersed in the prepared support (CNTs@FN) and contain a large amount of skeleton titanium, which shows extremely high activity and stability in propylene epoxidation reaction and also avoids the problem of separation of catalyst and product after reaction.…”
Section: Polymer Hydrogenation Catalystsmentioning
confidence: 99%